2007
DOI: 10.1111/j.1539-6924.2007.00964.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Screening Approach to Interpret Human Biomonitoring Data on Volatile Organic Compounds: Reverse Dosimetry on Biomonitoring Data for Trichloroethylene

Abstract: A screening approach is developed for volatile organic compounds (VOCs) to estimate exposures that correspond to levels measured in fluids and/or tissues in human biomonitoring studies. The approach makes use of a generic physiologically-based pharmacokinetic (PBPK) model coupled with exposure pattern characterization, Monte Carlo analysis, and quantitative structure property relationships (QSPRs). QSPRs are used for VOCs with minimal data to develop chemical-specific parameters needed for the PBPK model. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…In this way, compounds with similar properties can be grouped, and data for similar compounds can be used to fill gaps in the knowledge of a particular compound. For example, a recent study evaluated the possibility of predicting the in vivo kinetics of volatile organic compounds (VOCs) using PBBK models derived solely on the basis of physiological data and QSPR modeling (Liao et al, 2007). The authors concluded that acceptable predictions could be made for inhalation of lipophilic VOCs, such as trichloroethylene, but that the necessary QSPR algorithms were not available for water-soluble VOCs such as acetone.…”
Section: Overview Of Qivivementioning
confidence: 99%
“…In this way, compounds with similar properties can be grouped, and data for similar compounds can be used to fill gaps in the knowledge of a particular compound. For example, a recent study evaluated the possibility of predicting the in vivo kinetics of volatile organic compounds (VOCs) using PBBK models derived solely on the basis of physiological data and QSPR modeling (Liao et al, 2007). The authors concluded that acceptable predictions could be made for inhalation of lipophilic VOCs, such as trichloroethylene, but that the necessary QSPR algorithms were not available for water-soluble VOCs such as acetone.…”
Section: Overview Of Qivivementioning
confidence: 99%
“…Other approaches to interpretation of biomonitoring data in the context of current risk assessments include the application of 'reverse dosimetry' modeling in order to identify a possible distribution of external exposure levels that led to an observed distribution of measured biomarker concentrations in a population (Clewell et al, 2008;Georgopolous et al, 2009;Liao et al, 2007;Tan et al, 2007). As noted by numerous authors, the reverse dosimetry approach is computationally intensive, is data-set specific (a new reverse dosimetry modeling exercise is required for every set of biomonioring data) and is an attempt to address probabilistically what is an infinite-solution problem (Rigas et al, 2001;Georgopolous et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…To meet this need for methods, both forward dosimetry (Hays et al, 2007) and reverse dosimetry (Liao et al, 2007) approaches were developed that use pharmacokinetic tools to convert an applied dose for humans into an internal concentration (and vice versa ). By applying pharmacokinetic tools to existing chemical risk assessments, external safe doses, such as reference doses or tolerable daily intakes, or other dose response values, can be converted to corresponding biomarker concentrations in blood or urine, and with such a conversion, a comparison can then be made to the actual concentration measured by a human biomonitoring study.…”
Section: Biomonitoringmentioning
confidence: 99%